Probing the sp2 dependence of elastic moduli in ultrahard diamond films - Fyta, Maria G.; Hadjisavvas, George C.; Kelires, Pantelis C. (My University, 2007)
The structural and elastic properties of diamond nanocomposites and ultrananocrystalline diamond films (UNCD) are investigated using both empirical potentials and tight-binding schemes. We find that both materials are extremely hard, but their superb diamondlike properties are limited by their sp2 component. In diamond composites, the sp2 atoms are found in the matrix and far from the interface with the inclusion, and they are responsible for the softening of the material. In UNCD, the sp2 atoms are located in the grain boundaries. They offer relaxation mechanisms which relieve the strain but, on the other hand, impose deformations that lead to softening. The higher the sp2 component the less rigid these materials are.
Keywords: Carbon; Ultrananocrystalline diamond; Amorphous materials; Nanocomposite; Grain boundaries; Elastic properties